Prognostic value of changes in high-sensitivity cardiac troponin T beyond biological variation in stable outpatients with cardiovascular disease: a validation study - Biener, Moritz; Giannitsis, Evangelos; Hogrefe, Katharina; Müller-Hennessen, Matthias; Fröhlich, Hanna; Katus, Hugo; Frey, Norbert; Frankenstein, Lutz; Täger, Tobias (Clinical research in cardiology, 2022)
To evaluate the prognostic implications of longitudinal long-term changes beyond the biological variation of high-sensitivity cardiac troponin T (hs-cTnT) in outpatients with stable or asymptomatic cardiovascular disease (CV) and to assess possible differences in the prognostic value while using reference change value (RCV) and minimal important differences (MID) as metric for biological variation.